2009
DOI: 10.1007/s00592-009-0138-z
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and correlates of inadequate glycaemic control: results from a nationwide survey in 6,671 adults with diabetes in Brazil

Abstract: Diabetes is a significant public health burden on the basis of its increased incidence, morbidity, and mortality. This study aimed to estimate the prevalence of inadequate glycaemic control and its correlates in a large multicentre survey of Brazilian patients with diabetes. A cross-sectional study was conducted in a consecutive sample of patients aged 18 years or older with either type 1 or type 2 diabetes, attending health centres located in ten large cities in Brazil (response rate = 84%). Information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
90
7
29

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(141 citation statements)
references
References 34 publications
15
90
7
29
Order By: Relevance
“…Previous Brazilian data showed an even worse control rate among T1D patients over 18 years old (10%) [18]. Moreover, in a study that analyzed the control rate in Latin America, Chan et al [19] observed an overall control rate of 21.1%.…”
Section: Discussionmentioning
confidence: 93%
“…Previous Brazilian data showed an even worse control rate among T1D patients over 18 years old (10%) [18]. Moreover, in a study that analyzed the control rate in Latin America, Chan et al [19] observed an overall control rate of 21.1%.…”
Section: Discussionmentioning
confidence: 93%
“…In a study of subjects attending a primary care health unit in São Paulo, Brazil, Silva 18 found that 42% of diabetic patients had HbA1c levels below the 6.5% threshold, which is similar to the rate found by a national survey of specialized centers (46% of patients with HbA1c levels below the 7% threshold) 25 . On the other hand, another national survey of specialized centers found that only 27% of patients were below the 7% threshold 28 , and in a study of a sample attending a rehabilitation center, 24% of diabetic patients had HbA1c levels below 8% 24 . The results of studies outside Brazil vary greatly, ranging from a minimum of 16.7% of patients below the 7% threshold in a study of primary care units in Tunisia 29 Since hypertensive and diabetic subjects are at very high risk of cardiovascular complications, control of other cardiovascular risk factors should be an important part of healthcare.…”
Section: Discussionmentioning
confidence: 98%
“…However, the SERVIDIAH study shows that control of other cardiovascular risk factors is less than satisfactory. The high prevalence of overweight and obesity is a general finding in most studies of hypertensive and/or type 2 diabetic patients 15,16,18,28,33 . It is also striking to note the low proportion of subjects that adhere to weight-loss diets (16.1% of hypertensive subjects and 13.6% of diabetic subjects).…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas recentes têm demonstrado que é muito difícil manter os níveis de HbA 1c abaixo de oito mesmo em centros de referência. Uma pesquisa brasileira recente mostrou que 90% de 979 jovens de diferentes regiões do país não estavam com seus níveis de HbA 1c bem controlados 12,13 .…”
Section: Discussionunclassified